The equation 25 = 9x^2 - 30x has to be solved for x.

25 = 9x^2 - 30x

=> 9x^2 - 30x - 25 = 0

x1 = `(30 - sqrt(30^2 + 900))/18`

=> x1 = `5/3 - (5*sqrt 2)/3`

x2 = `5/3 + (5*sqrt 2)/3`

**The solution of 25 = 9x^2 - 30x is x = `5/3 - (5*sqrt 2)/3` and x = `5/3 + (5*sqrt 2)/3` **

The equation 25=9x^2-30x can be written in form ax^2+bx+c=0 as under:

9x^2 - 30x -25 = 0, where a=9, b=-30 and c=-25

The two roots x1 and x2 are given as:

x1 = (-b+sqrt(b^2-4*a*c))/(-2a) and

x2 = (-b-sqrt(b^2-4*a*c))/(-2a)

Hence

x1 = (-(-30)+sqrt((-30)^2-4*9*(-25)) / (-2*9)

x1 = (30+sqrt(900+900)) / 18 = (30+30*sqrt(2))/18

x1 = 5/3 + 5*sqrt(2)/3 and

x2 = (-(-30)-sqrt((-30)^2-4*9*(-25)) / (-2*9)

x2 = 5/3 - 5*sqrt(2)/3

**Solution of equation 25 = 9x^2 - 30x is**

**x = 5/3 + 5*sqrt(2)/3 ** and **x = 5/3 - 5*sqrt(2)/3**